MATHEMATICS PRE-SERVICE TEACHERS’ DIGITAL LITERACY AND THEIR READINESS TOWARDS 21ST CENTURY LEARNING: A MIXED METHOD STUDY - Soeparno, Pranata Lulus; Ismaniati, Christina (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The rapid advancement of technology in Indonesia seems not in line with its utilization, especially in the educational field. According to studies, Indonesian teachers are not ready to implement ICT in their classrooms. Furthermore, most elderly teachers are not sensitive enough to technology changes. When it comes to emergency teaching and learning in the pandemic era, teachers as predicted do not have enough capacity to maximize the use of ICT as the only source. This study aims to find out: (1) if the lack of digital literacy skills already happened in college, and (2) pre-service teachers' readiness to face 21st century education. As the result, this study could not prove that the lack of digital skills occurs in college. The digital literacy skills of pre-service are good (77,6%) and they have received multimedia learning subject from university. Related to their readiness toward 21st century learning, most of them claimed not yet ready because of the lack of skills and knowledge in implementing ICT and because of the lack of ICT facility support.